GPR for large-scale estimation of groundwater recharge distribution - Strobach, Elmar; Harris, Brett; Dupuis, Christian; Martin, M. (IBAM, 2010)
The Gnangara Mound, north of Perth, Western Australia, has been investigated using Ground-Penetrating Radar (GPR). Several hundred line-kilometers of GPR of common offset data have been acquired over an area of approximately 800 km2. The acquisition of these datatasets was performed at two different center frequencies (50 and 250 MHz)in order to better resolve the complexity of the hydrogeological targets of interest which are water retentive layers found above the water table. These layers impede the recharge of the surficial aquifer and may have important impact on local ecosystems but also on the management of the ground water resource. The data presented here-in demonstrate the successful imaging of the regional water table and of these water retentive layers. For thefirst time, these data provide insight into the spatial distribution and the continuity of these water retentive layers and provide important information to be included in the flow modeling of the ground water in this region of the world.